Prevalence and Associated Factors of Dynapenia, Pre-Sarcopenia, and Sarcopenia in Korean Adults: A Cross-Sectional Epidemiological Study - Do-Youn Lee (Medicina)
Background and Objectives: This study examined the prevalence and risk factors of dynapenia, pre-sarcopenia, and sarcopenia among Korean adults using nationally representative data. Materials and Methods: A cross-sectional analysis was conducted using the 2022–2023 Korea National Health and Nutrition Examination Survey (KNHANES). Participants aged 20 years and older with available muscle strength and body composition measurements were included. Handgrip strength and skeletal muscle mass (measured via bioelectrical impedance analysis) were used to classify participants based on the Asian Working Group for Sarcopenia (AWGS) 2019 criteria. Logistic regression analysis identified associated risk factors. Results: The prevalence of pre-sarcopenia, dynapenia, and sarcopenia was 9.6%, 3.4%, and 1.6%, respectively. Pre-sarcopenia was most common across all age groups, while sarcopenia was primarily observed in older adults (p < 0.001). Age was a key predictor for all three conditions (p < 0.001), with sex differences—men had a higher prevalence of pre-sarcopenia (p = 0.014), whereas women showed higher rates of dynapenia (p = 0.003) and sarcopenia (p = 0.008). Low physical activity (p < 0.001), high stress (p = 0.021), and smoking (p = 0.012) were also significant risk factors. Conclusions: These findings highlight the importance of early identification and targeted interventions to prevent muscle deterioration. Public health strategies focusing on lifestyle modifications and sex-specific approaches may help mitigate the burden of sarcopenia and its related health complications in aging populations.